Maternal and child health global challenges, programs, and policies - Ehiri, John (Springer US, 2009)
Maternal and Child Health: Global Challenges, Programs, and Policies Edited by John Ehiri, PhD, MPH, MSc (Econ.) Our current era of globalization, war, and socioeconomic unrest has revealed public health as a worldwide concern and a major frontier for social justice with maternal and child health at its epicenter. Yet, there has been a relative scarcity of textbooks specifically dedicated to this crucial area. Maternal and Child Health: Global Challenges, Programs, and Policies addresses this gap by analyzing the range of socioeconomic and environmental factors, health care disparities, politics, policies, and cultural practices that impact the health and safety of mothers, as well as the well-being and optimum development of their children. Individual sections focus on unequal distribution of the world’s resources, politics and power, specific disease concerns, programs, policies and emerging concerns with a focus on what is currently being done, and what needs to be done to improve the health status of women, children, and adolescents. The book’s contributors are some of the world’s most respected experts, carefully selected to represent different global geographic regions and diverse professional disciplines related to maternal and child health from both academic and field practice perspectives. Among the topics in this authoritative volume: The impact of war, globalization, gender inequity, and harmful traditional practices (e.g., female genital mutilation). Specific health concerns, including tuberculosis, malaria, HIV, and malnutrition. Child and adolescent health issues, from abuse and neglect to children in difficult circumstances. Pregnancy-related issues: safety, abortion and post-abortion care, teen pregnancy, and more. Strategies for planning, developing, and maintaining maternal and child health systems in developing countries.The status of global initiatives, such as Integrated Management of Childhood Illnesses and the Millennium Development Goals. The status of evidence-based maternal and child health in the developing world. With such a wealth of information on both practical and conceptual levels, Maternal and Child Health: Global Challenges, Programs, and Policies is as relevant to students and researchers in the field as it is to policy makers and those working for global health and development organizations. Each chapter features discussion questions and learning objectives, making this book an excellent stand-alone text for courses in global health in general and global maternal and child health in particular. The world’s heterogeneity - A history of international cooperation in maternal and child health - Global burden of disease among women, children, and adolescents - Promotion of global perinatal health - Maternal and child health in the organization for economic cooperation and development (oecd) countries - Health system impacts on maternal and child health - The environment and maternal and child health - Politics, power, and maternal and child health - Impact of wars and conflict on maternal and child health - The impact of globalization on maternal and child health - Gender equity: perspectives on maternal and child health - Harmful traditional practices and women’s health: female genital mutilation - Abortion and postabortion care - Specific disease concerns - Malaria in women and children - The global burden of childhood diarrhea - Tuberculosis in childhood and pregnancy - Impact of hiv on the health of women, children, and families in less developed countries - Malnutrition and maternal and child health - The global burden of obstetric fistulas - Health challenges for women, children, and adolescents with disabilities - Unintentional injuries in children - Programs, policies, and emerging concerns - Evidence-based maternal and child health - A global perspective on teen pregnancy - Progress and challenges in making pregnancy safer: a global perspective - Global immunization challenge: progress and opportunities - Adolescent health - The global burden of child maltreatment - Children in difficult circumstances - Integrated management of childhood illness - Planning, development, and maintenance of the mch workforce - An agenda for child health policy in developing countries.